TRANSFORMASI IDEOLOGI HARITI DI BALI - I Nyoman Rema (Forum Arkeologi, 2017)
Brayut legend is very popular in Bali. It is the legend of the conjugal life which had eighteen children. This legend is often associated with Hariti mythology, which also had many children. The purpose of this research is to determine the transformation of Hariti ideology in Bali. The result of this research is some varieties of media transformation of Hariti ideologi such as statues, folklore, legends, literary works such as poems about Brayut geguritan. Balinese people rarely know the name of Hariti. It is known that a family or a statue that has many children as Berayut. Nevertheless, the transformation of Hariti ideology from India to Bali, certainly not taken for granted, but adapted to the local culture of Balinese people. So, it really can be internalized and implemented in everyday life, in term of protection to children.